Targets and Sources of Oral Corrective Feedback in English as a Foreign Language Classrooms: Are Students' and Teachers' Beliefs Aligned? - Ha, Xuan Van; Nguyen, Loc Tan (Frontiers in Psychology, 2021)
Recent decades have witnessed extensive research focusing on oral corrective feedback (CF), a key aspect of English as a second/foreign language (ESL/EFL) learning and teaching, but relatively little research has examined the relationship between learner and teacher beliefs about CF. The study reported in this article investigated the relationship between teacher and learner beliefs regarding the optimal targets and sources of CF in Vietnamese secondary EFL contexts. Data which were collected at four Vietnamese public high schools included questionnaires completed by 250 students, interviews with 15 of them, and interviews with 24 teachers. The findings showed that the students were happy to receive CF to all types of errors, including less important errors such as those not influencing their communicative success. The teachers were generally more selective in their choices of error types, but they sometimes faced some tensions between their overall teaching objective and the students' practical needs to learn the material that would be tested in subsequent exams. Regarding CF sources, the students preferred teacher correction to self-correction or peer correction although they believed that self-correction was effective for their learning and wished their teachers would provide them with training on how to conduct peer correction and self-correction. The teachers also thought that it was part of their role to be the main CF providers to ensure the accuracy of classroom feedback. Some teachers were skeptical about their students' ability to provide peer CF. Pedagogical implications are discussed.